Alkaloids, Coumarin and Cinnamic Acid Derivative from Murraya koenigii (Linn.) Spreng. - Tahia, Faiza; Sikder, Md Al Amin; Haque, Mohammad Rashedul; Shilpi, Jamil A; Awang, Khalijah; Mansur, Md Abdullah Al; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2015)
A total of seven compounds were isolated from the methanol extract of leaves of Murraya koenigii (Linn.) Spreng. The isolated compounds were characterized as arborinine (1), ferulic acid (2), umbelliferone (3), mahanimbine (4), koenimbine (5), koenidine (6) and O-demethyl murrayanine (7) by extensive spectroscopic studies, including high field NMR analysis as well as co-TLC with authentic samples, whenever possible. This is the first report of occurrence of arborinine (1) and ferulic acid (2) from Murraya species. Dhaka Univ. J. Pharm. Sci. 14(1): 29-33, 2015 (June)